Normal mitral cell dendritic development in the setting of Mecp2 mutation - Palmer, Amy M. (2012)
Rett syndrome (RTT) is an autism spectrum disorder caused by mutation in the gene encoding methyl CpG binding protein 2 (MECP2). Evidence to date suggests that these disorders display defects in synaptic organization and plasticity. A hallmark of the pathology in RTT has been identified as decreased dendritic arborization, which has been interpreted to represent abnormal dendritic formation and pruning during development. Our previous studies revealed that olfactory axons display defective pathfinding and targeting in the setting of Mecp2 mutation. In the present work, we use Mecp2 mutant mouse models and the olfactory system to investigate dendritic development. Here, we demonstrate that mitral cell dendritic development proceeds normally in mutant mice, resulting in typical dendritic morphology at early postnatal ages. We also failed to detect abnormalities in dendritic inputs at symptomatic stages when glomeruli from mutant mice appear smaller in area than the wild type (WT) (6 weeks postnatally). Collectively, these findings suggest that the initial defects in glomeruli impairment seen with Mecp2 mutation do not result from abnormal dendritic development.Our results using the olfactory system indicate that dendritic abnormalities are not an early feature in the abnormalities incurred by Mecp2 mutation.